2020
DOI: 10.1167/iovs.61.6.59
|View full text |Cite
|
Sign up to set email alerts
|

Macular Thickness in Intermediate Age-Related Macular Degeneration Is Influenced by Disease Severity and Subretinal Drusenoid Deposit Presence

Abstract: To investigate how macular thickness varies with intermediate age-related macular degeneration (iAMD) severity and the presence of subretinal drusenoid deposits (SDDs). METHODS. A longitudinal prospective study of 143 participants >50 years of age with no to intermediate AMD who were followed with multimodal imaging and functional testing. Participants were stratified by iAMD severity according to imaging features. Macular thicknesses measurements over the central circles with 1-mm, 3-mm, and 6-mm diameters ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Recently Chiang et al carried out a study of the retinal macular thickness (including the central 1 mm area) in patients with SDD, patients with various degrees of AMD, and a control group. Their study of the inner retina showed a trend of retinal thickness reduction in the central 1 mm area in patients with SDD compared to controls [ 32 ]. Our study showed a reduction of the inner retina thickness in the central 1 mm area in patients with CD and in patients with SDD compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Chiang et al carried out a study of the retinal macular thickness (including the central 1 mm area) in patients with SDD, patients with various degrees of AMD, and a control group. Their study of the inner retina showed a trend of retinal thickness reduction in the central 1 mm area in patients with SDD compared to controls [ 32 ]. Our study showed a reduction of the inner retina thickness in the central 1 mm area in patients with CD and in patients with SDD compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the subretinal presence of RPD is associated with RPE and photoreceptor disruption ( Greferath et al, 2016 ). Clinical data from intermediate AMD patients indicate that RPD are associated with decreased photoreceptor function ( Flamendorf et al, 2015 ), choroidal changes ( Keenan et al, 2020 ), and over time with increased retinal thinning and degeneration ( Chiang et al, 2020 ). The histological studies that have been undertaken show RPD to contain similar components to drusen such as photoreceptor outer segment debris including opsins; lipid in the form of unesterified cholesterol; RPE fragments (melanolipofuscin granules); ApoE, a protein important for lipid trafficking; vitronectin; and the immunogenic protein, CFH ( Rudolf et al, 2008 ; Greferath et al, 2016 ; Wu et al, 2022 ).…”
Section: The Role Of the Retinal Pigment Epithelium In Retinal Homeos...mentioning
confidence: 99%
“…Interestingly, compared with control eyes without large drusen or SDDs, the central maculas of eyes at lower risk with unilateral large drusen were thicker, whereas higher-risk eyes with SDDs were thinner in cross-sectional multivariate analyses, suggesting that macular thickness in intermediate AMD varies with disease severity and that there were small increases in eyes with large drusen and decreases in eyes with SDDs. The investigators assumed that active processes possibly related to neuroinflammation and neurodegeneration may be contributory to such biphasic changes [ 33 ]. Regarding the choroidal changes, early AMD seems to undergo biphasic alterations similarly; initially, choroidal volume and choroidal vascular index increased during early drusen formation but decreased thereafter.…”
Section: Stratifying the Risk Of Advanced Amd: Emerging Drusen Subtyp...mentioning
confidence: 99%